KALKULASI EFISIENSI, KONDISI JPO, DAN NORMA SOSIAL: PERILAKU MAHASISWA MENYEBERANG TANPA MELALUI JEMBATAN PENYEBERANGAN ORANG - Yatti Rosmiati, Yatti Rosmiati; Akhmad Nana Makmur, Akhmad Nana Makmur; Heri Kurnia, Heri Kurnia; Akhirudin, Akhirudin; Mas Fierna Janvierna Lusie Putri, Mas Fierna Janvierna Lusie Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Pedestrian overpass (PDO) are constructed to ensure the safety of pedestrians; however, a paradox arises when many university students who are considered educated individuals choose not to use them. This study aims to understand the reasons behind students’ avoidance of pedestrian bridges through a grounded theory approach. Data were collected through in-depth interviews with 20 students, behavioral observations, and field notes, and analyzed using open coding, axial coding, and selective coding. The findings reveal three main categories: efficiency calculation, in which students perceive that using pedestrian bridges is not worth the cost in terms of time and effort; bridge conditions, which are often regarded as dark, dirty, uncomfortable, and unsafe; and urban social and cultural norms, where jaywalking is considered socially acceptable because it is practiced by the majority. This study recommends multidimensional interventions, including improving bridge design, fostering new social norms that emphasize safety, and implementing integrated policies that balance design, education, and law enforcement.